Conservation enforcement: Insights from people incarcerated for wildlife crimes in Nepal. Issue 2 (15th December 2019) - Paudel, Kumar; Potter, Gary R.; Phelps, Jacob
ABSTRACT: There are long‐standing debates about the effectiveness and social impacts of enforcement‐based conservation, particularly as investments into enforcement increase in response to growing alarm about Illegal Wildlife Trade (IWT). However, there is little data on the people subject to this enforcement, including prison sentences, species targeted, what motivates and deters them, and the social impacts of enforcement. This study identified 384 individuals across Nepal who were in prison for IWT offences in late 2016, and involved interviews ( n = 116) focused on respondents' trade practices, economic circumstances and motivations. IWT prisoners represented 10–20% of the total prison populations in two regions and often received stiff sanctions, with a range of downstream impacts on respondents' families. Most respondents were arrested for their involvement in the rhinoceros trade (61%). Most were poor (56%) and from indigenous communities (75%), highlighting potentially inequitable impacts of enforcement. Despite common assumptions about the links between IWT, poverty and organized crime, most respondents were motivated by the desire to earn extra income and by the ease of IWT compared to other employment. IWT was neither a primary livelihood strategy, nor had the attributes for formal organized crime. Respondents, particularly poor respondents, seemed to underestimate the risks of detection and incompletely understood the scale of sanctions. Improved public awareness about the scale and social impacts of sanctions could help increase deterrence effects while reducing unintended social harms of enforcement.